2007
DOI: 10.1007/s10464-007-9109-0
|View full text |Cite
|
Sign up to set email alerts
|

Putting the system back into systems change: a framework for understanding and changing organizational and community systems

Abstract: Systems change has emerged as a dominant frame through which local, state, and national funders and practitioners across a wide array of fields approach their work. In most of these efforts, change agents and scholars strive to shift human services and community systems to create better and more just outcomes and improve the status quo. Despite this, there is a dearth of frameworks that scholars, practitioners, and funders can draw upon to aid them in understanding, designing, and assessing this process from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
402
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(442 citation statements)
references
References 40 publications
12
402
0
8
Order By: Relevance
“…These interviews provided information to assess the attributes of the interviewee and other infl uential stakeholders (ie, self-reporting and peer-reporting) and provided further insights into network and power dynamics and case studies. In Kenya and Bangladesh, this research shows that a handful of catalytic individuals, well-connected and trusted in their formal and informal social networks, 84,85 have played a crucial part in transfer of information, changing of perceptions, and resolving of confl icts; achievements that have proven essential to advance the nutrition agenda in the context of fragmentation and competing interests between and within various groups of stakeholders. 23,82,86,87 Preliminary fi ndings show that these individuals have, in addition to extensive knowledge and experience in nutrition, relatively strongly developed stakeholder awareness and perspective awareness.…”
Section: Panel 6: What Makes a Nutrition Champion?mentioning
confidence: 95%
“…These interviews provided information to assess the attributes of the interviewee and other infl uential stakeholders (ie, self-reporting and peer-reporting) and provided further insights into network and power dynamics and case studies. In Kenya and Bangladesh, this research shows that a handful of catalytic individuals, well-connected and trusted in their formal and informal social networks, 84,85 have played a crucial part in transfer of information, changing of perceptions, and resolving of confl icts; achievements that have proven essential to advance the nutrition agenda in the context of fragmentation and competing interests between and within various groups of stakeholders. 23,82,86,87 Preliminary fi ndings show that these individuals have, in addition to extensive knowledge and experience in nutrition, relatively strongly developed stakeholder awareness and perspective awareness.…”
Section: Panel 6: What Makes a Nutrition Champion?mentioning
confidence: 95%
“…Systems change has its theoretical roots in open systems theory and seeks to explain how the different parts of a social system interact to produce meaningful and transformative change (Linkins, Brya, and Chandler 2008;Foster-Fishman and Behrens 2007;Foster-Fishman, Nowell, and Yang 2007;Parsons 2007;Tseng and Seidman 2007;Supovitz and Taylor 2005). These kinds of efforts are especially prevalent in health and human services.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…A system is contrasted with a confined domain such as one organization or even one program within an organization (indeed, complex organizations might be considered micro-systems themselves). In the public and nonprofit sectors, examples of systems include a school district and a human service delivery network (Foster-Fishman, Nowell, and Yang 2007;Supovitz and Taylor 2005). In most cases, systems change requires change in policies and practices in an inter-organizational context; that is, multiple organizations must implement individual organizational change in a way that ensures alignment with desired broader, macro-level change efforts (Isett and Provan 2005;Fernandez and Rainey 2006).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Using system thinking and the perspective of organizational change, Foster-Fishman, Nowell, & Yang (2007) proposed a framework to understand the system-part interaction and mechanism, in order to lever system change. In their framework, they suggested that system norms, resources, regulations and operations be further examined to reveal the root causes and bring about system change.…”
Section: Systems Perspectivementioning
confidence: 99%